Unlocking India’s hospital beds: why a digital portal is the cure for a stretched system - Rajasundar, Harikarthikeyan Karuthamalai (International Journal Of Community Medicine And Public Health, 2026)
India’s health system faces chronic resource gaps and inefficiencies. With public health spending at only 1.84% of GDP and very low hospital bed densities (around 0.6 beds per 1000 population), simply adding beds is unaffordable and slow. A more efficient alternative is to improve utilisation: a real-time digital platform that tracks staffed bed availability can raise effective capacity and reduce inequity. Early experiments – from Delhi’s COVID-19 bed portal to the bed management system in AIG Hospitals, Hyderabad – show substantially higher occupancy and throughput. International evidence also supports these results, confirming that real-time tracking systems can deliver major efficiency gains. This brief proposes piloting a national bed-tracking dashboard and shows it can yield large gains for much lower cost and risk than new construction, with safeguards to address data accuracy, incentives and privacy. These promising results are tempered by limited evidence from a small number of pilots and by systemic constraints such as staff shortages, uneven digital readiness, and governance challenges that will require independent evaluation and safeguards during scale-up.